Theoretical proposal of civic journalism and its effect on the digital scene - Mateus Borea, Julio (2012)
The growing presence of Internet and social networks into the structure of social information and their integration into traditional journalism, give the idea of a shift in the relationship between media and its users, placing them as partners in the development of public agendas. However, the change seems to focus on the activation of parallel information systems, remote from the original proposal of Civic Journalism. The purpose of this paper is to recover the meaning and the original proposals of this current, distinguishing it from functional uses that Internet provides to the media today. At the same time, investigates the model at theoretical and methodological level, rescuing the few cases in the country.